The ultimate urban makeover : unique architectural renovations - Crafti, Stephen (Mulgrave, Vic. : Images Pub., 2007)
Contains details on domestic extensions, renovations and makeovers and includes plans.
Keywords: Architecture, Domestic; Buildings -- Repair and reconstruction; Buildings -- Additions -- Design and construction; Decoration and ornament, Architectural; Architecture, Domestic -- Designs and plans